Increased Antiviral Treatment Among Hospitalized Children and Adults With Laboratory-Confirmed Influenza, 2010–2015. (23rd December 2016) - Appiah, Grace D; Chaves, Sandra S; Kirley, Pam D; Miller, Lisa; Meek, James; Anderson, Evan; Oni, Oluwakemi; Ryan, Patricia; Eckel, Seth; Lynfield, Ruth; Bargsten, Marisa; Zansky, Shelley M; et al.
Abstract: Using population-based surveillance data, we analyzed antiviral treatment among hospitalized patients with laboratory-confirmed influenza. Treatment increased after the influenza A(H1N1) 2009 pandemic from 72% in 2010–2011 to 89% in 2014–2015 ( P < .001). Overall, treatment was higher in adults (86%) than in children (72%); only 56% of cases received antivirals on the day of admission.